Bacterial Translocation as a Cause of Postoperative Sepsis in Surgical Patients Undergoing Laparotomy - Thapa, Neeraj; Hamal, Bhairav Kumar; Yadav, Nagendra Prasad; Thapa, Ghanshaym (Journal of Lumbini Medical College, 2016)
Introduction: Bacterial translocation is the invasion of indigenous intestinal bacteria through the gut mucosa to normally sterile tissues and the internal organs. Objective of the study is to examine the spectrum of bacteria involved in translocation in surgical patients undergoing laparotomy and to determine the relation between nodal migration of bacteria and the development of postoperative septic complications. Methods: Mesenteric lymph nodes (MLN) culture was done in patients undergoing elective and emergency surgeries fulfilling the inclusion criteria. Results: Bacterial translocation was identified in 22 (44.8%) patients. The most common organism identified was Escherichia coli (n=11, 50%). Both enteric bacteria, typical of indigenous intestinal flora, and non-enteric bacteria were isolated. Postoperative septic complications developed in four (11%) patients. Septic morbidity was more frequent when a greater diversity of bacteria resided within the mesenteric lymph nodes. Conclusion: Bacterial translocation is associated with an increase in the development of postoperative sepsis in surgical patients. The organisms responsible for septic morbidity are similar in spectrum to those observed in the mesenteric lymph nodes. These data strongly support the gut origin hypothesis of sepsis in humans. Besides, there is increased bacterial translocation in patients undergoing emergency procedures. Journal of Lumbini Medical College. 2014;2(2):28-30.